Choosing Exchange Regimes in the Middle East and North Africa. (Pamphlet Series; Pamphlet Series, No., 2003)
This paper reviews the exchange regimes of five emerging market countries in the Middle East and North Africa region-Egypt, Jordan, Lebanon, Morocco, and Tunisia-and one oil-exporting country-Iran-to see whether they need to consider adopting more flexible arrangements as they further open their economies to trade and capital flows.